On induced modules over locally Abelian-by-polycyclic groups of finite rank - Tushev, A.V. (Доповіді НАН України, 2019)
We develop some methods for studying the modules over group rings, which are based on properties of induced modules and on the embedding of these modules in the modules over rings of quotients of group rings. Using these methods, we have obtained the criteria of primitivity for group algebras of certain classes of locally soluble groups.